Use of complementary and alternative medicine and low quality of life associate with the need for psychological and psychotherapeutic interventions in inflammatory bowel disease. Issue 1 (18th February 2021) - Kutschera, Maximilian; Waldhör, Thomas; Gröchenig, Hans Peter; Haas, Thomas; Wenzl, Heimo; Steiner, Pius; Koch, Robert; Feichtenschlager, Thomas; Eckhardt, Gerald; Mayer, Andreas; Kirchgatterer, Andreas; Ludwiczek, Othmar; et al.
Abstract: Introduction: Patients with inflammatory bowel disease (IBD) suffer from various symptoms, impairing their quality of life and often affecting psychosocial issues. This may lead to the need for additional psychological care. This study investigated patients' subjective need for integrated psychosomatic support and psychotherapy and indicators for it. Materials and methods: This is a cross‐sectional multicentre study in Austrian IBD patients who were in routine care at 18 IBD outpatient clinics. Patients filled in an anonymous, validated questionnaire (Assessment of the Demand for Additional Psychological Treatment Questionnaire [ADAPT]) assessing the need for psychological care. The ADAPT gives two separate scores: the need for integrated psychosomatic support and for psychotherapy. In addition, health‐related quality of life and the use of complementary and alternative medicine as well as clinical and socio‐demographic variables were queried. Multivariable regression analysis was performed to estimate the effect of the previously mentioned variables on the need for additional psychological care. Results: Of 1286 patients, 29.7% expressed a need for additional psychological care, 19.6% expressed a need for integrated psychosomatic support and 20.2% expressed a need for psychotherapy. In the multivariable analysis, the two strongest indicators for the need for both types of psychological care were the use of complementary and alternative medicine (for integrated psychosomatic support: odds ratio = 1.64, 95% confidence interval 1.13–2.39, p = 0.010; for psychotherapy: odds ratio = 1.74, 95% confidence interval 1.20–2.53, p = 0.004), and a low health‐related quality of life score (for integrated psychosomatic support: odds ratio = 0.95, 95% confidence interval 0.94–0.96, p < 0.001; for psychotherapy: odds ratio = 0.96, 95% confidence interval 0.94–0.97, p < 0.001). Discussion: About 30% of the Austrian IBD patients expressed a need for integrated psychosomatic support and/or psychotherapy. The most important indicators for this need were the use of complementary and alternative medicine and low quality of life. Key summary: What is already known? Despite ongoing improvement of treatment options, patients may not respond to treatment or may develop side effects. Due to this burden of disease, patients may also suffer from psychological symptoms, such as depression In our previous study in 2008, we found that 31% of patients with inflammatory bowel disease (IBD) expressed a subjective need for psychological interventions What are the significant and/or new findings of the study? Despite improvements in therapy, around 30% of patients with IBD express a subjective need for psychological interventions This subjective need for psychological interventions is associated with complementary and alternative medicine use and low quality of life